Novel Mutations in PTH1R Associated with Primary Failure of Eruption and Osteoarthritis. (February 2014) - Frazier-Bowers, S.A.; Hendricks, H.M.; Wright, J.T.; Lee, J.; Long, K.; Dibble, C.F.; Bencharit, S.
Autosomal dominant mutations in PTH1R segregate with primary failure of eruption (PFE), marked by clinical eruption failure of adult teeth without mechanical obstruction. While the diagnosis of PFE conveys a poor dental prognosis, there are no reports of PFE patients who carry PTH1R mutations and exhibit any other skeletal problems. We performed polymerase chain reaction–based mutational analysis of the PTH1R gene to determine the genetic contribution of PTH1R in 10 families with PFE. Sequence analysis of the coding regions and intron-exon boundaries of the PTH1R gene in 10 families ( n = 54) and 7 isolated individuals revealed 2 novel autosomal dominant mutations in PTH1R (c.996_997insC and C.572delA) that occur in the coding region and result in a truncated protein. One family showed incomplete penetrance. Of 10 families diagnosed with PFE, 8 did not reveal functional (nonsynonymous) mutations in PTH1R ; furthermore, 4 families and 1 sporadic case carried synonymous single-nucleotide polymorphisms. Five PFE patients in 2 families carried PTH1R mutations and presented with osteoarthritis. We propose that the autosomal dominant mutations of PTH1R that cause PFE may also be associated with osteoarthritis; a dose-dependent model may explain isolated PFE and osteoarthritis in the absence of other known symptoms in the skeletal system.